Intraflagellar transport 20 promotes collective cancer cell invasion by regulating polarized organization of Golgi‐associated microtubules. Issue 4 (28th February 2019) - Aoki, Tomoaki; Nishita, Michiru; Sonoda, Junya; Ikeda, Taro; Kakeji, Yoshihiro; Minami, Yasuhiro
Abstract : Collective invasion is an important strategy of cancers of epithelial origin, including colorectal cancer (CRC), to infiltrate efficiently into local tissues as collective cell groups. Within the groups, cells at the invasive front, called leader cells, are highly polarized and motile, thereby providing the migratory traction that guides the follower cells. However, its underlying mechanisms remain unclear. We have previously shown that signaling emanating from the receptor tyrosine kinase Ror2 can promote invasion of human osteosarcoma cells and that intraflagellar transport 20 (IFT20) mediates its signaling to regulate Golgi structure and transport. Herein, we investigated the role of Ror2 and IFT20 in collective invasion of CRC cells, where Ror2 expression is either silenced or nonsilenced. We show by cell biological analyses that IFT20 promotes collective invasion of CRC cells, irrespective of expression and function of Ror2. Intraflagellar transport 20 is required for organization of Golgi‐associated, stabilized microtubules, oriented toward the direction of invasion in leader cells. Our results also indicate that IFT20 promotes reorientation of the Golgi apparatus toward the front side of leader cells. Live cell imaging of the microtubule plus‐end binding protein EB1 revealed that IFT20 is required for continuous polarized microtubule growth in leader cells. These results indicate that IFT20 plays an important role in collective invasion of CRC cells by regulating organization of Golgi‐associated, stabilized microtubules and Golgi polarity in leader cells. Abstract : Our results indicate that intraflagellar transport 20 promotes collective invasion of colorectal cancer cells, irrespective of expression status and function of Ror2, through organization of Golgi‐associated, stabilized microtubules, oriented toward the direction of invasion in cells at the invasive front.